Detection of very high energy radiation from HESS J1908+063 confirms the Milagro unidentified source MGRO J1908+06 - Aharonian, F.; Akhperjanian, A. G.; Anton, Gisela; De Almeida, U. Barres; Bazer-Bachi, A. R.; Becherini, Y.; Behera, B.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bochow, A.; Borrel, V.; et al. (Astronomy & Astrophysics, 2009)
Aims. Detection of a γ-ray source above 300 GeV is reported, confirming the unidentified source MGRO J1908+06, discovered by the Milagro collaboration at a median energy of 20 TeV. Methods. The source was observed during 27 h as part of the extension of the HESS Galactic plane survey to longitudes >30°. Results. HESS J108+063 is detected at a significance level of 10.9σ with an integral flux above 1 TeV of (3.76 ± 0.29 ph cm s, and a spectral photon index Γ = 2.10 ± 0.07 ± 0.2. The positions and fluxes of HESS J1908+063 and MGRO J1908+06 are in good agreement. Possible counterparts at other wavelengths and the origin of the γ-ray emission are discussed. The nearby unidentified GeV source, GRO J1908+0556 (GeV) which also remains unidentified and the new Fermi pulsar 0FGL J1907.5+0617, may be connected to the TeV source. © ESO 2009.
Keywords: Gamma rays; Observations